Sacral Chordoma Metastatic to Bilateral Clavicle - A Rare Clinical Presentation and Review of Literature - Agrawal, Rashi; De, Sudarsan; Srivastava, Alpana; Gupta, Sweety; Singh, Dinesh; Agrawal, Sandeep (Asian Journal of Medical Sciences, 2013)
Chordoma is an uncommon tumor , so the metastatic cases generally are given more attention. Various cases with central nervous system involvement, cutaneous and mandible metastases have been reported. Metastases to bone is noted in literature but metastases to bilateral clavicle is not reported yet to the best of our knowledge. We hereby present a rare case of sacral chordoma with clavicular metastases. Asian Journal of Medical Science, Volume-4 (2013), Pages 24-27 DOI: http://dx.doi.org/10.3126/ajms.v4i4.7999